The Effectiveness of Lavender Aromatherapy in Treating Sleep Disorders in Third Trimester Pregnant Women at the Bongo Nol Community Health Center - Yuliyani Masimudati; Tut Rayani Aksohini Wijayanti (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Sleep disorders are a common complaint among pregnant women, especially in the third trimester, and have the potential to negatively impact maternal well-being and pregnancy outcomes. Physiological, hormonal, and psychological changes during pregnancy increase the risk of decreased sleep quality, while pharmacological therapy options are limited due to safety considerations. Therefore, safe and easy-to-apply non-pharmacological interventions are needed. This study aimed to analyze the effectiveness of lavender aromatherapy in overcoming sleep disorders in third trimester pregnant women at the Bongo Nol Community Health Center. The study used a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 30 third trimester pregnant women selected purposively. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after the administration of lavender aromatherapy through inhalation for seven consecutive days. Data analysis was performed using the Wilcoxon signed-rank test. The results showed a significant decrease in PSQI scores after the intervention, indicating an improvement in sleep quality among the respondents. Lavender aromatherapy proved to be effective as a non-pharmacological intervention in reducing sleep disturbances in pregnant women in their third trimester. In conclusion, lavender aromatherapy can be considered a safe, simple, and applicable complementary therapy to improve the sleep quality of pregnant women in primary health care.